State funded Muslim schools?: equality, identity and community in multifaith Britain - Tinker, Claire (2006)
In this thesis I explore the debate over the state funding of Muslim schools in Britain, examining the arguments used for and against by the stakeholders involved. Qualitative interviews were conducted with head teachers, politicians, Muslim parents and representatives from a number of stakeholder organisations, to identify their reasons for supporting or opposing state funded Muslim schools.